Public policy modeling and applications - Fuentes, Miguel Angel (2019)
Two expected results of public policies are fostering economic development and show adaptive capacity in case of disruptions. e latter is linked to the concept of resilience. In the research paper by G. Castañeda and O. A. Guerrero, the Resilience of Public Policies in Economic Development, the authors analyze how the adaptive capacity of the policy- making process generates resilience in the face of disruptions. Further, they develop a computational model, which takes into account different social mechanisms (coevolutionary learning and complex interaction networks) to compute a resilience score against simulated disruptions to the expected evolution. Interestingly, they show that certain policy issues are resilient and others fragile, depending on the context of application.